Rapid Prototyping and Evaluation for Green Manufacturing - Afzeri Tamsir; Rudi Irawan; Riza Muhida (International Journal of Engineering Science and Technology Development (IJEST), 2013)
With global awareness of environmental risk and the pressing needs to improve efficiency, manufacturing systems are growing into new concept. Green manufacturing is reflected to employ various green strategies and technique to produce with eco-efficient. Green manufacturing aspects on the machine level were studied in various machining process. On this paper presentsthe green manufacturing review of Rapid Prototyping process. The objective is to evaluate the factors involved in green process of RP.Several comparative RP process respect to green manufacturing criteria are described.Rapid Prototyping process uses three dimensional CAD files to fabricate a physical model. Models are usually made from variety of material such as ABS, rubber and specific metals. Each material has the environment impact during the process and recycling.RP process are known as process not suitable for making direct product. However, lates technology makes it suitableto produce the parts with reasonable cost. For near the future, the utilization of this technology is becoming increasing and green manufacturing effect should be considered.Based on study conducted, several type of RP process is eco-efficient due to amount of waste material produced and environment impact during the process.